Engaging employees through high involvement work practices - Konrad, Alison M. (Henry Stewart Talks, 2009)
What is employee engagement?, Organizational benefits of engagement, Are high involvement practices effective?, Goal achievement, How often are high involvement practices used?, Benefits of a participatory change process, The impact of workplace diversity, Innovation